3D Anisotropic Stress Analysis during Kyropoulos Growth of Sapphire Single Crystal. Issue 8 (22nd July 2019) - Zermout, S.; Mokhtari, F.; Nehari, A.; Lasloudji, I.; Haddad, F.; Merah, A.
Abstract: By using 3D finite element calculations, numerical simulations are performed to predict the thermal field as well as the thermal stress in a c ‐axis sapphire single crystal grown by Kyropoulos technique. The effects of additional resistive heating (placed under the crucible bottom) and crystal rotation are investigated and a comparison is made between the isotropic and anisotropic analysis. The anisotropy of the elastic constants and thermal expansion coefficients as well as their temperature dependence are considered in the anisotropy calculations while Young's modulus and the Poisson ratio are used in the isotropic analysis. Thermal stress is found to be smaller in the anisotropy analysis than that in the isotropic analysis and significant differences are found in their respective distribution patterns. Additional resistive heating acts to decrease both of the crystal–melt interface convexity and the von Mises stress. In addition, crystal rotation combined with additional resistive heating decreases significantly the thermal stress inside the sapphire crystal and along the melt–crystal interface. Therefore, optimizing the heating conditions and using a suitable crystal rotation rate seem to be favorable to control the growth interface shape and to reduce thermal‐stress‐related defects during the growth process. Abstract : Crystal anisotropy and temperature dependency of thermal expansion and elasticity coefficients have to be considered in the thermal stress computation. The combination of crystal rotation and additional resistive heating at the bottom of Kyropoulos crucible leads to a significant decrease in the von Mises stress. The relationship between temperature nonlinearity and thermal stress has been clearly illustrated in this work.